Conducta obstétrica en paciente primigesta de 18 años con 30 semanas de gestación más diabetes gestacional. - Pazmiño Saltos Danna Alejandra (2022)
To establish the Obstetrical Conduct in an 18-year-old prim gestational patient with 30 weeks of gestation plus gestational diabetes. Blood biometry, blood chemistry and insulin, general urine test were performed. Fetal well-being was evaluated based on maternal perception, ultrasound visualization of fetal movements, fetal growth, evaluation of amniotic fluid volume and fetal umbilical artery blood flow resistance, evaluated by color Doppler. The fetus reported an estimated weight of 5500gr which contraindicated a vaginal delivery and elective cesarean section was chosen at 38 weeks of gestation to have a perfect state between mother and child since at 30 weeks of gestation she had a weight of 3450gr compatible with macrosomic fetus so obstetric surveillance and recording of maternal glycemia levels were performed to make timely decisions. On admission to her cesarean section, she presented normal glycemia values, alert state of consciousness, a macrosomic product with adequate Apgar was obtained and she was born without any novelty, her normal glycemia values were normal and she did not contract her mother's disease. A glycemia test was performed on the mother and the newborn and subsequent controls were suggested for opportune detection of type 2 Diabetes Mellitus in the mother and Infantile Diabetes in the newborn.